Status of Philosophy - Karosas, Justinas (Problemos, 1990)
In its origin the philosophy of K. Marx is the philosophy of practice. But practice is always social in its character. And that is why the philosophy should have nothing in common with the naturalistic tradition and pure gnoseologism. Nevertheless, in its academic practice the philosophy is partitioned into general one (dialectical materialism) and special one (historical materialism). The first part of the philosophy is based upon the concept of practice, but the social character of the latter is adequately analysed only in the second part of the philosophy. This inconsistency leads to the positivistic and naturalistic relicts in the Marxist philosophy.